Storage of Mortgage Maximum in Indonesia Lawyers Club Episode Events (When Ahok Apologizes) - Syahrul, Abdul (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2017)
This research aims at describing and explaining the deviation â€œleechâ€ on maxim courtesy at the event of Indonesia Lawyers Club "After Ahok Apologize" Â The method used in this research use as descriptive analysis method and content analysis. The results show that the most distorted maxim, is the maxim of appreciation, wisdom and generosity. The most distorted indicators on the maxim award of speaker award used direct speech in arguing, refuting, and criticizing. While at the maxim of wisdom and generosity, the most violated indicator is that the speaker rejected the opinion of other speakers withouth saying â€œsorryâ€ or asking forgiveness.